Low-Cost Wearable Device for Sleepiness Detection Based on Heart Rate Monitoring - Marvin Yonathan Hadiyanto; Ananda Keshava; Budi Harsono; Shoaib Aslam (Advance Sustainable Science Engineering and Technology, 2024)
Driver sleepiness is one of the most contributing factors in car accidents. Preventions to this problem have been made with various types of driver’s sleepiness detection system, such as systems based on face detection and electrocardiography approaches. However, these approaches require sophisticated systems and impractical design that are not suitable for the low- cost wearable device for daily use. Photoplethysmography based sensor is very favorable to be implemented in the low-cost wearable device to monitor the driver’s heart rate due to its reliability in measurement and simplicity in design. In this study we propose a photoplethysmography based wearable device that is low-cost, wearable, simple to build, and good reliability. We have shown that our wearable device exhibits less than 3.12 BPM in average absolute error heart rate with the standard instruments, moreover, our low-cost wearable device is successfully detecting sleepiness based on heart rate reduction of the subjects, which in sleepy condition the heart rate decreases typically ~30 % from the normal condition. Here, we design a sleepiness detection device with 3 levels of sleepiness alarm based on heart rate reduction that is very promising to be implemented as a wearable device in daily use for car drivers to prevent accidents due to sleepiness factor. In the future, this concept can be further improved as a smart driver monitoring system that can monitor physical conditions, mental conditions, and driver’s behavior particularly for the upcoming era of semi-autonomous and autonomous car.